Evaluation of The Use Prophylactic Antibiotics in Caesarean Surgery Patients - Devi Ristian Octavia (Indonesian Journal of Health Research, 2019)
Introduction. The incidence of cesarean section is increasing year by year in various countries including Indonesia. Provision of prophylactic antibiotics is an attempt to prevent infection. Antibiotics given to surgical patients aim to reduce the number of bacterial colonies, reduce the amount of contamination inoculum so as to reduce the risk of infection or as a therapy if it has been previously infected. The research that has been done is an observational study with retrospective data obtained from the patient's medical record.